Effectiveness of personalized face-to-face and telephone nursing counseling interventions for cardiovascular risk factors: A controlled clinical trial - Vílchez Barboza, Vivian (2016)
Objective: to evaluate the effect and gender differences of an innovative intervention involving in-person and telephone nursing counseling to control cardiovascular risk factors (arterial hypertension, dyslipidemia, and overweight), improve health-related quality of life and strengthen self-efficacy and social support in persons using the municipal health centers' cardiovascular health program. Method: a randomized controlled clinical trial involving participants randomized into the intervention group who received traditional consultation plus personalized and telephone nursing counseling for 7 months (n = 53) and the control group (n = 56). The study followed the Consolidated Standards of Reporting Trials Statement. Results: women in the intervention group presented a significant increase in the physical and mental health components compared to the control group, with decreases in weight, abdominal circumference, total cholesterol, low-density lipoprotein cholesterol, and the atherogenic index. The effects attributable to the intervention in the men in the intervention group were increased physical and emotional roles and decreased systolic and diastolic pressure, waist circumference, total cholesterol, low-density lipoprotein cholesterol, atherogenic index, cardiovascular risk factor, and 10-year coronary risk. Conclusion: this intervention is an effective strategy for the control of three cardiovascular risk factors and the improvement of health-related quality of life.